Evaluation of tomatoes fruits flesh colour, beta-carotene and lycopene content - Soytong, M.; Guevarra, P. R.; Mateo, J. M. C.; Galvez, H. F. (International Journal of Agricultural Technology, 2021)
The phenotypes of tomatoes in various varieties (lines) were investigated including lycopene and beta-carotenet contents on tomato flesh fruits. Results showed that the fruits of var SL08 (N30B Orange) gave the highest lycopene and tomato var SA (40A Red) gave the lowest lycopene. Moreover, tomato var. SL06 (39B Pink) has the highest beta-carotene content and tomato var. SL02 (33A Yellow-Orange) has the lowest beta-carotene content. It can be concluded that phenotype characters of tomato varieties (lines) in colour of flesh fruits are related to lycopene and beta-carotene content. These preliminary results can be used for further investigation of different genotypes of tomato and relate its fruit flesh colour to the expression of target genes, lycopene beta-cyclase and lycopene epsilon-cyclase genes.